The Impact of COVID-19 Pandemic on the Surgical Treatment of Orthopedic Trauma in a Tertiary Hospital in Portugal - Ferreira, David; Ramos, Filipe; Pinheiro, Joana; Soares do Brito, Joaquim; Martins, Samuel; Sarmento, Marco (Gazeta Médica, 2022)
INTRODUCTION: The impact of the COVID-19 pandemic on orthopedic trauma surgery is not well characterized in the literature. We provided an evaluation of such impact in a tertiary hospital in Portugal. MATERIAL AND METHODS: Retrospective analysis of the patients admitted for surgical treatment due to acute orthopedic trauma from March to December of 2019 and March to December of 2020. RESULTS: A total of 794 patients in 2019 and 728 in 2020 were included. Although the mean time to surgery was shorter the hospital stay was longer in 2020. Infected patients had a longer hospital stay and longer time until surgery compared to non-infected. There was no significant difference between the mortality and need for treatment in the intensive care unit (ICU) in both years. There was a significant increase in the number of polytrauma patients treated in our institution in 2020 compared to 2019. CONCLUSION: Orthopedic trauma surgery was globally influenced by the pandemic. Safe and effective measures should be adopted in the treatment of trauma patients, to reduce the clinical and economic impact.